Automated Drip Irrigation System Based on IoT for Chili Plants Using Solar Panel Energy - Lamasigi, Zulfrianto Yusrin; Haba, Abd. Rahmat Karim; Jafar, Muh. Iqbal; Syamsir, Syamsir; Hulukati, Stephan A. (Jurnal Pengabdian Masyarakat, 2024)
Purpose: This research paper aims to address the challenges faced by horticultural farmers in Lauwonu Village, particularly regarding water scarcity exacerbated by hot weather conditions. The study emphasizes the significance of utilizing technology, specifically a drip irrigation system based on IoT and solar panel energy, to mitigate these challenges effectively. Method: The research employed a qualitative approach to investigate the impact of implementing IoT-based drip irrigation systems on chili farming productivity. Data collection methods included surveys and interviews with 15 members of the Mekar Green farmer group. Thematic analysis was utilized to interpret the gathered data. Practical Applications: The findings demonstrate the practical benefits of adopting IoT-driven irrigation technology, enhancing water efficiency and agricultural productivity. This research offers valuable insights for farmers, policymakers, and agricultural practitioners, facilitating informed decision-making and sustainable agricultural practices.Conclusion: Implementing IoT-enabled drip irrigation systems powered by solar panels presents a viable solution to address water scarcity challenges in chili farming. The study underscores the importance of leveraging technology to improve agricultural resilience and productivity, thereby contributing to sustainable food production and livelihoods in rural communities.